2019
DOI: 10.1002/admi.201900788
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iron–Nickel Sulfide Porous Nanosheets via a Chemical Etching/Anion Exchange Method for Efficient Oxygen Evolution Reaction in Alkaline Media

Abstract: and so on. Among them, Ni-based materials, especially Ni 3 S 2 , have been extensively studied for use as an effective OER catalyst owing to its inherent advantages of good conductivity and unique 3D configuration. However, widespread use of Ni 3 S 2 electrocatalysts is still severely restricted by their low surface area exposure and poor electrocatalytic stability. [24,25] To overcome the above issues, it is vital to design efficient strategies to optimize the catalytic performances of the electrocatalysts. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Therefore, the two components synergistically improved the overall OER performance (Figure 11 e and f). Jiang and co-workers [98] prepared iron-nickel sulfide nanosheets (FeS-Ni 3 S 2 /NF) with interpenetrated porous 3D-networks through a partial chemical etching reaction. Physical characterization showed that the unique interpenetrating porous 3D network structure exposed large active sites and effectively improved the proton transfer and charge transport.…”
Section: D Electrodes For the Oermentioning
confidence: 99%
“…Therefore, the two components synergistically improved the overall OER performance (Figure 11 e and f). Jiang and co-workers [98] prepared iron-nickel sulfide nanosheets (FeS-Ni 3 S 2 /NF) with interpenetrated porous 3D-networks through a partial chemical etching reaction. Physical characterization showed that the unique interpenetrating porous 3D network structure exposed large active sites and effectively improved the proton transfer and charge transport.…”
Section: D Electrodes For the Oermentioning
confidence: 99%
“…Prussian blue analogues (PBAs) with open frameworks are a class of metal–organic framework family, which contain transition metals (TMs) orderly coordinated with the ligands of the cyan group (CN – ). , The diversity of TM ions enables PBAs with easily tunable physicochemical properties and endows them with the potential applications for OER. , At present, PBAs have been widely utilized as the powerful precursors for the synthesis of various nanomaterials, such as nitrides, sulfides, , brides, phosphides, and oxides. , However, the pyrolysis at high temperatures leads to the sharp collapse of the framework structures of PBAs on account of the uncontrolled removal of the CN – ligand, which induces a serious aggregation of their derivatives and cannot make full use of the structural advantages of PBAs . Additionally, the current research based on PBA derivatives mainly focus on the powder state, whereas the PBAs with multilevel nanostructures directly grown on metal substrates can expose more active sites and facilitate the charge-transfer process .…”
Section: Introductionmentioning
confidence: 99%
“…After long-term exploration by researchers, numerous non-noble metal-based electrocatalysts have been reported in recent years, especially transition-metal-based catalysts, for example, transition-metal alloys, , oxides, , sulfides, , phosphides, , and so forth. Among these, transition-metal phosphides were widely concerned relying on their unique electronic structure and catalytic effect, regarded as a kind of promising non-noble metal catalysts. , Plentiful monometallic phosphides, such as FeP, CoP, and Ni 2 P, have been already investigated and used as catalysts in the electrochemical field, showing pretty good electrocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting high-efficiency and low-cost multifunctional electrocatalysts is still imperative as well as challenging. 10,11 After long-term exploration by researchers, numerous nonnoble metal-based electrocatalysts have been reported in recent years, especially transition-metal-based catalysts, for example, transition-metal alloys, 12,13 oxides, 14,15 sulfides, 16,17 phosphides, 18,19 and so forth. Among these, transition-metal phosphides were widely concerned relying on their unique electronic structure and catalytic effect, regarded as a kind of promising non-noble metal catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%